Progesterone - a new look at an old drug - Малгожата Зыгмунт; Яцек Сапа (Publishing House TRILIST, 2017)
On the basis of the literature the role of progesterone in contemporary medicine was described, having regard to different routes of administration. Review of the available literature on the role of progesterone in modern obstetric practice says that after 80 years of application of this steroid, it has the potential to continue to be used in clinical practice. The replacement of exogenous progesterone is a recognized treatment for a hormonal deficiency, which occurs in the II phase of the menstrual cycle and during pregnancy endangered, and his future in gynecology and obstetrics is not under threat. Conversely, it can be said that it is of great interest, particularly in view of new possibilities for vaginal or sublingual administration route. An additional advantage is the new direction of action, used in medicine - an anticonvulsant and neuroprotective, antimigraine. Review of the literature confirms that more safety is characterized by the treatment of lutein ailments using natural rather than synthetic progesterone, which indicates good tolerability of the hormone replacement. These diverse and divergent effects of progesterone as well as selective modulators of the progesterone receptor on the body of a woman possible through specific nuclear progesterone receptor, which are located in the target cell, including a mucous membrane of the uterus, breast, central nervous system and pituitary gland